2023
DOI: 10.3390/ijerph20043250
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Local Variations and the Determinants of Childhood Stunting in Nigeria

Abstract: Introduction: Understanding the specific geospatial variations in childhood stunting is essential for aligning appropriate health services to where new and/or additional nutritional interventions are required to achieve the Sustainable Development Goals (SDGs) and national targets. Objectives: We described local variations in the prevalence of childhood stunting at the second administrative level and its determinants in Nigeria after accounting for the influence of geospatial dependencies. Methods: This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
1
2
1
Order By: Relevance
“…The finding of our study regarding the geographical distribution of stunting is consistent with previous studies in Ethiopia, which consistently report a higher prevalence of stunting among children in the Tigray, Afar, and Amhara regions [50,51]. Studies conducted in Rwanda and Nigeria also showed a wide geographical variation of childhood stunting [52,53]. The highest stunting prevalence of the northern part of Ethiopia can possibly be attributed to political instability and environmental emergencies [54,55].…”
Section: Discussionsupporting
confidence: 91%
“…The finding of our study regarding the geographical distribution of stunting is consistent with previous studies in Ethiopia, which consistently report a higher prevalence of stunting among children in the Tigray, Afar, and Amhara regions [50,51]. Studies conducted in Rwanda and Nigeria also showed a wide geographical variation of childhood stunting [52,53]. The highest stunting prevalence of the northern part of Ethiopia can possibly be attributed to political instability and environmental emergencies [54,55].…”
Section: Discussionsupporting
confidence: 91%
“…We were also unable to identify associations between stunting, being underweight, and wasting and micronutrient deficiency (ferritin, RBP) or insufficiency (vitamin D). The data do not confirm other findings of higher prevalence of stunting in HEU than HUU infants [ 58 ], but they indicate that stunting, although decreasing, still affected a significant proportion of pre-school infants in Africa, irrespective of maternal HIV status, possibly due to socioeconomic and demographic factors [ 57 , 59 , 60 , 61 , 62 , 63 ]. Overall, the findings suggest that the current population of HIV-exposed infants does not need specific interventions regarding the nutritional aspects evaluated, because the deficiencies observed involved similarly HIV-exposed and HIV-unexposed infants.…”
Section: Discussioncontrasting
confidence: 83%
“…Spatial analysis of stunting cases in Kerinci Regency, Indonesia, is crucial for understanding the distribution patterns and identifying hotspots of stunting prevalence. Previous studies have highlighted the significance of geographic distribution in health issues like stunting, emphasizing the need for targeted interventions based on spatial data (Ahmed et al, 2023;Kuse & Debeko, 2023;Sipahutar et al, 2021).…”
Section: Discussionmentioning
confidence: 99%